Пізньосередньовічна накладка із зображенням дракона з розкопок 1936 р. на Старокиївській горі - Осипенко, М.С. (Археологія, 2016)
Публікацію присвячено виготовленій з кольорового металу цікавій знахідці, знайденій на Старокиївській горі неподалік Десятинної церкви — пізньосередньовічній литій накладці із зображенням міфічної істоти. Проведено атрибуцію, встановлено дату побутування та поширення, а також зроблено припущення щодо місця виготовлення предмету. Today, a great part of documentation concerning the research of Starokyivska mountain and the surrounding areas in the first half of the 20th century are lost. This fact complicates the work with the findings which are not presented to the scientific circles. One of such findings is a casted bronze (?) plate of pentagonal shape with a relief depiction of a mythical creature, namely, a dragon. During the work with an item, it was ascertained thatsuch type of findings belongsto the elements of design of decoration assemblage on leather bags-kalytas and was presented on them by pairwise depictions of dragons on the items of various size: appliques, plates, cover plates of locks, etc. The ornamentation peculiarities of analogous products contain a certain heraldic implication related to the community of ancient Novgorod, which is ascertained by stylistically similar depictions on hanging lead stamps of the period from the 14th to the 16th centuries, and on products made of metal and bone. Regardless of final identification of the finding, and coming from the geography of such items’ spread, we can see that Novgorod was economically active at the known trade routes in Eastern Europe until the second half of the 16th century. На сегодняшний день утрачено большую часть документации по исследованиям Старокиевской горы и окрестной территорий в первой половине ХХ в. Это усложняет работу с находками, которые еще не вошли в научный оборот. Одна из таких находок — литая бронзовая (?) накладка пятиконечной формы с рельефным изображением мифического существа — дракона. В ходе работы с изделием установлено, что такой тип находок принадлежит к элементам оформления декоративного ансамбля кожаных сумок-калит, где, зачастую, был представлен попарным изображениям драконов на предметах разной величины — накладки, пластины, лучины замков и др. В особенностях орнаментации аналогических изделий заложен некий геральдический подтекст, связанный с общиной древнего Новгорода, что подтверждается стилистически похожими изображениями на новгородских вислых свинцовых печатях ХIV—XVІ вв., металлических и костяных изделиях. Независимо от окончательной идентификации находки и исходя из географии распространения подобных вещей, видим, что экономическая активность Новгорода на известных торговых путях Восточной Европы проводилась вплоть до второй половины ХVІ в.